1988
DOI: 10.1002/j.1460-2075.1988.tb02828.x
|View full text |Cite
|
Sign up to set email alerts
|

The multicopy appearance of a large inverted duplication and the sequence at the inversion joint suggest a new model for gene amplification.

Abstract: The amplified DNA of HC50474, a Chinese hamster fibroblast cell line selected in three steps for high resistance to coformycin, consists chiefly of 150 copies of a large inverted duplication including the adenylate deaminase gene. Most if not all of these units are more than 2 x 120 kb long. The inverted duplication was first detected in the cells recovered from the second selection step, at the same chromosomal location as the first step amplified units. Its formation and amplification appear to be coupled si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
1
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 48 publications
4
78
1
1
Order By: Relevance
“…6C), coupled with appropriate end ligation reactions, will produce circular amplicons and a broken chromosome terminated by sequences homologous to some of those in the amplicon. Circles produced by four breaks/ligations will contain imperfect inverted repeats of the type typically found in mammalian amplicons (Ford and Fried 1986;Saito and Stark 1986;Looney and Hamlin 1987;Passananti et al 1987;Hyrien et al 1988;Ruiz and Wahl 1988). The sizes of such extrachromosomal amplicons could easily conform to the majority of amplicon sizes detected at the CHO DHFR locus (Looney et al 1988).…”
Section: A Model For Gene Amplification Involving Chromosome Breakagementioning
confidence: 99%
“…6C), coupled with appropriate end ligation reactions, will produce circular amplicons and a broken chromosome terminated by sequences homologous to some of those in the amplicon. Circles produced by four breaks/ligations will contain imperfect inverted repeats of the type typically found in mammalian amplicons (Ford and Fried 1986;Saito and Stark 1986;Looney and Hamlin 1987;Passananti et al 1987;Hyrien et al 1988;Ruiz and Wahl 1988). The sizes of such extrachromosomal amplicons could easily conform to the majority of amplicon sizes detected at the CHO DHFR locus (Looney et al 1988).…”
Section: A Model For Gene Amplification Involving Chromosome Breakagementioning
confidence: 99%
“…In many cases characterized, these amplified regions contain large ''head-to-head'' duplications (palindromes) of sequences that can be tens to hundreds of kb in size (3)(4)(5)(6)(7)(8). Cytogenetic studies have further revealed that large inverted duplications of a chromosomal region are formed at early stages of gene amplification (9)(10)(11).…”
mentioning
confidence: 99%
“…The presence of inverted beta-satellite blocks flanking the ZNF gene may have promoted further duplication events. Such large palindromes have been shown to promote gene amplification somatically (Hyrien et al 1988;Windle and Wahl 1992) and are found associated with other duplicated gene family clusters (Bishop et al 1985;Gao et al 1997;Groot et al 1990). Due to the potential selective advantage of expressed ZNF genes within the repeat structure, evolutionary pressure may have favored expansion over contraction of this region, leading to the generation of a large cluster of tandemly duplicated genes in the human genome (Figure 7).…”
Section: Discussionmentioning
confidence: 99%